Transforming Education Through Technological Innovation In The Face Of The Era Of Society 5.0 - Legi, Hendrik; Damanik, Dapot; Giban, Yoel (ARKA INSTITUTE, 2023)
Technological and industrial developments have reached Society 5.0, and education today is centered on a balance where the Internet is not only a medium of information but plays a role in living life. The formulation of the problem in this study is how education transforms education in Indonesia in facing the era of Society 5.0. The purpose of this research is to explain how education is transformed in facing the era of Society 5.0. The research method used is qualitative descriptive with literature studies. This study concludes that technological developments cannot be avoided, so we must be able to adapt and respond to these developments. The era of Society 5.0 is marked by rapid technological development and integration between humans and technology. The transformation of education has become very important in this era, where the need for digital skills, creativity, collaboration, and problem-solving is increasing. Technological innovation is critical in changing how education is delivered, accesses information, and interacts between learners and educators. This article discusses how technological innovation can change the education paradigm, facilitate active and collaborative learning, and improve the quality of education in the era of Society 5.0.